2016
DOI: 10.2533/chimia.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Lithium/Element Exchange as an Efficient Tool for Accessing Atropo-enriched Biaryls via Arynes

Abstract: This account documents the development of transition metal-free, aryne-mediated aryl-aryl coupling, the 'ARYNE coupling', which began in 2001 in Lausanne. ortho,ortho'-Di-, tri- and even tetrasubstituted biphenyls have now become accessible on a multi-gram scale. The reaction is perfectly regioselective and the obtained polybromobiphenyls can be submitted to regioselective bromine/lithium interconversions. The access to enantiopure biphenyls is now possible using enantiopure sulfoxides as chiral auxiliaries, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In this context, Leroux et al reported an efficient transition metal free aryl‐aryl coupling protocol, the so‐called “Aryne coupling” reaction . Very recently, we extended the reaction to the construction of hetaryl‐aryl backbones, developing thus the “(Het)‐Aryne” version of the reaction (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Leroux et al reported an efficient transition metal free aryl‐aryl coupling protocol, the so‐called “Aryne coupling” reaction . Very recently, we extended the reaction to the construction of hetaryl‐aryl backbones, developing thus the “(Het)‐Aryne” version of the reaction (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Leroux et al reported an efficient transition metal free aryl-aryl coupling protocol, the so-called "Aryne coupling" reaction. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Very recently, we extended the reaction to the construction of hetaryl-aryl backbones, developing thus the "(Het)-Aryne" version of the reaction (Scheme 1). [44] However, our study essentially focused on the thiophene ring as a model partner.…”
Section: Introductionmentioning
confidence: 99%
“…Chirality at the molecular scale is a property of growing importance in chemical and physical sciences, as well as in medicine and technology. 10 Various additions to the electrophilic triple bond of ortho-arynes have largely been employed for the synthesis of chiral biaryls through the formation of the biaryl C(sp 2 )−C(sp 2 ) single bond, 1,8,9,11 and some helicenes have also been derived from arynes. 12,13 Recently, the palladium-catalyzed cyclotrimeriza-tion of rac-7,8- [5]helicyne (1, Figure 1b) was reported for the stereoselective syntheses of chiral nanographenes embedding up to six [5]helicene units.…”
mentioning
confidence: 99%
“…Chirality at the molecular scale is a property of growing importance in chemical and physical sciences, as well as in medicine and technology . Various additions to the electrophilic triple bond of ortho -arynes have largely been employed for the synthesis of chiral biaryls through the formation of the biaryl C­(sp 2 )–C­(sp 2 ) single bond, ,,, and some helicenes have also been derived from arynes. , Recently, the palladium-catalyzed cyclotrimerization of rac- 7,8-[5]­helicyne ( 1 , Figure b) was reported for the stereoselective syntheses of chiral nanographenes embedding up to six [5]­helicene units. rac -7,8-[5]­Helicyne ( 1 ) is an inherently chiral ortho -aryne, the first of its kind, and no enantioenriched inherently chiral aryne is known. Herein, we propose to extend the synthetic chemistry of arynes to chiral and enantioenriched aryne atropisomers 2 bearing a biaryl stereogenic axis vicinal to the reactive aryne triple bond (Figure b).…”
mentioning
confidence: 99%